Completion of pressure testing, rectification and replacement of the defective spare parts of the supplied and installed flush valves - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the completion of pressure testing, rectification and replacement of the defective spare parts of the supplied and installed flush valves of BRACU new campus project.